Work Stress in Nurses and Its Influence on Patient Care and Quality of Life - Anwar, Bushra; Akhtar, Naseem; Parveen, Sumera; Sher, Nuzhat (Biological and Clinical Sciences Research Journal, 2025)
Nurses play a critical role in patient care, but work-related stress is a prevalent concern that negatively affects their quality of life (QoL) and caring behaviors. High stress levels can lead to burnout, decreased job satisfaction, and compromised patient care. Understanding the impact of work stress on nurses’ well-being and professional performance is essential for improving healthcare outcomes. Objective: To assess the work stress in nurses and its impact on their quality of life and patient care. Methodology: A cross-sectional study was conducted in the Nursing Department of Medicare Hospital, Multan from December 2023 to December 2024. One hundred nurses with at least 1-year experience and those directly involved with patient care were selected for the study. Data was collected through a questionnaire divided into four sections; demographic details, Expanded Nurses Stress Scale, Quality of Life questionnaire, and Caring Dimension Inventory. Results: The mean stress score was 2.81 ± 0.49 with the highest score from death and dying and inadequate emotional preparation. The mean quality of life score was 57.57 ± 17.98, with better physical health core than mental health. Gender was significantly associated with quality of life with males scoring better than females. Job stress score and subsets were negatively associated with total caring behavior score. However, caring behavior was only significantly related to the total score, problems with the supervisor, intra-physician conflict, and patients and families. The variables of job stress were inversely associated with quality of life with job stress causing a 28% change in quality of life (R2adj = 0.281, p<0.001). Conclusion: There was high job stress among nurses, which negatively affected their quality of life and caring behaviors.